2017
DOI: 10.7448/ias.20.1.21409
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of HIV prevalence and service use in East Zimbabwe: implications for future targeting of interventions

Abstract: Introduction: Focusing resources for HIV control on geographic areas of greatest need in countries with generalized epidemics has been recommended to increase cost-effectiveness. However, socioeconomic inequalities between areas of high and low prevalence could raise equity concerns and have been largely overlooked. We describe spatial patterns in HIV prevalence in east Zimbabwe and test for inequalities in accessibility and uptake of HIV services prior to the introduction of spatially-targeted programmes. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
(38 reference statements)
5
19
0
Order By: Relevance
“…Thirteen studies used the Kulldorff spatial scan statistic [15] to identify clustering of HIV infection, [1624], HIV-specific and all-cause mortality [25–27], and sero-discordant partnerships [28]. In these studies, the spatial scan statistic identified statistically significant “hotspots” or “cold spots” by systematically scanning circular windows of varying sizes across the study area, comparing the number of cases within the window to those outside the window.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies used the Kulldorff spatial scan statistic [15] to identify clustering of HIV infection, [1624], HIV-specific and all-cause mortality [25–27], and sero-discordant partnerships [28]. In these studies, the spatial scan statistic identified statistically significant “hotspots” or “cold spots” by systematically scanning circular windows of varying sizes across the study area, comparing the number of cases within the window to those outside the window.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that socioeconomic and demographic factors are important predictors of HIV transmission, which necessitates interprofessional collaborations between basic and social scientists, including geographers in HIV and AIDS, in resource-limited countries. There has been considerable research to investigate the geographical variation of the HIV epidemic in sub-Saharan Africa [7][8][9][10][11]. After almost four decades of research, we have comprehensive knowledge of the factors associated with HIV infection in sub-Saharan Africa [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These models identified significant geographically-focused patterns that would not have been accounted for by standard regression procedures [ 18 ]. The use of spatial cluster techniques to identify clusters of HIV prevalence enhanced the understanding of the determinants of HIV infection and geographic patterns, leading to improved resource allocation in Zimbabwe [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Properly designed and executed bio-behavioral surveys aim to obtain a probability sample of the population in contrast to health sector or program data, which have data only from clients using their services. Surveys can provide an independent evidence-based assessment of gaps in coverage for programs and health facilities and identify emerging epidemics [ 37 , 38 ]. Moreover, validated survey modules on HIV stigma, the accessibility of health services, violence, and sexual behavior can provide more in-depth information on sensitive topics and allow analysis to identify and explore associations between HIV infection and barriers to accessing prevention and other services to guide the implementation of programs.…”
Section: Resultsmentioning
confidence: 99%